Bolivia: the sinking of the Constituent Assembly and the collapse of the constitutional project - Zalles, Alberto (2008)
Bolivia is closing a chapter of its recent political history, one in which the Constituent Assembly has achieved little more than accentuating the existing structural problems in society. A constitutional project with a philosophy grounded in the multiethnic nature of society and the collective aspirations towards social justice, has been unable to forge either a national pact or a simple plan to move towards a new form of state institutionalization. The political change heralded so far has been hampered by the centralist decision-making practices of the MAS (Movement Towards Socialism), the strategic ineffectiveness of the political operators and the excessive foreign policy dependency. In spite of the turbulent domestic setting, the Bolivian crisis could be tempered by the positive constellation of external regional factors. Brazil, an emerging power, followed by both Argentina and Chile, look likely to consolidate a region that is free of conflict in the Southern Cone.